Photocatalytic reduction of Cs(I) ions removed by combined maghemite-titania PVA-alginate beads from aqueous solution. (15th April 2017) - Majidnia, Zohreh; Fulazzaky, Mohamad Ali
Abstract: The presence of Cs(I) ions in nuclear wastewater becomes an important issue for the reason of its high toxicity. The development of adsorbent embedded metal-based catalysts that has sufficient adsorption capacity is expected for the removal of Cs(I) ions from contaminated water. This study tested the use of maghemite, titania and combined maghemite-titania polyvinyl alcohol (PVA)-alginate beads as an adsorbent to remove Cs(I) ions from aqueous solution with the variables of pH and initial concentration using batch experiments under sunlight. The results showed that the use of combined maghemite-titania PVA-alginate beads can have an efficiency of 93.1% better than the use of either maghemite PVA-alginate beads with an efficiency of 91.8% or titania PVA-alginate beads with an efficiency of 90.1%. The experimental data for adsorption of Cs(I) ions from aqueous solution with the initial concentrations of 50, 100 and 200 mg L −1 on the surface of combined maghemite-titania PVA-alginate beads were well fit by the pseudo-second-order and Langmuir models. The optimal adsorption of Cs(I) ions from aqueous solution by combined maghemite-titania PVA-alginate beads under sunlight occurs at pH 8 with an initial Cs(I) ion concentration of 50 mg L −1 . The combined maghemite-titania PVA-alginate beads can be recycled at least five times with a slight loss of their original properties. Graphical abstract: Photocatalytic reduction and adsorption of Cs(I) ions onto combined maghemite-titania PVA-alginate in aqueous solution and then desorption of Cs(0) from combined maghemite-titania PVA-Alginate in HCl 0.1 M solution. Highlights: Synthesis of combined TiO2 and γ-Fe2 O3 embedded in PVA-alginate beads were performed. Sythesised beads were used with different variables to remove Cs(I) ions from aqueous solution. Experimental data were well fit by the pseudo-second-order and Langmuir models. Optimal adsorption of Cs(I) ions occured at pH 8 with C 0  = 50 mg L −1 . Sythesised beads can be reused at least five times with slight loss of original properties.